2018
DOI: 10.2196/jmir.8986
|View full text |Cite
|
Sign up to set email alerts
|

How Online Quality Ratings Influence Patients’ Choice of Medical Providers: Controlled Experimental Survey Study

Abstract: BackgroundIn recent years, the information environment for patients to learn about physician quality is being rapidly changed by Web-based ratings from both commercial and government efforts. However, little is known about how various types of Web-based ratings affect individuals’ choice of physicians.ObjectiveThe objective of this research was to measure the relative importance of Web-based quality ratings from governmental and commercial agencies on individuals’ choice of primary care physicians.MethodsIn a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 40 publications
0
39
0
Order By: Relevance
“…From a consumer’s perspective, patients need to know that only a small number of physicians have been reviewed online and the average rating score for a physician might not be sufficient for choosing a doctor as assumed, given the tendency of consumers to provide feedback on experiences that are unusually positive or negative. As posting the health care experience becomes more commonplace, we anticipate a “consumer’s guide” to help patients navigate the PORs and make more informed choices [92,93].…”
Section: Discussionmentioning
confidence: 99%
“…From a consumer’s perspective, patients need to know that only a small number of physicians have been reviewed online and the average rating score for a physician might not be sufficient for choosing a doctor as assumed, given the tendency of consumers to provide feedback on experiences that are unusually positive or negative. As posting the health care experience becomes more commonplace, we anticipate a “consumer’s guide” to help patients navigate the PORs and make more informed choices [92,93].…”
Section: Discussionmentioning
confidence: 99%
“…Further, the large numbers of reviews we found may address some of the concerns about lack of an adequate sample (because health systems can also wait to post reviews until a sufficient number are collected or can use older surveys to increase the numbers of reviews and narratives) [12,25]. However, it has been reported that patients use reviews from different sources differently, and this makes it difficult to extrapolate how patients will view star ratings and comments posted by health systems [26]. At least one recent study suggests that patients trust commercial rating sites more than health systems’ sites [27].…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, choosing the right physician is critical for patients because health care services are related to health and life [11,12]. However, because of information asymmetry and lack of professional health care knowledge, it is difficult for patients to ascertain a physician’s competency and service quality based on the limited information and knowledge they obtain [13]. Telemedicine markets should provide efficient and adequate information to help patients make decisions about using such services.…”
Section: Introductionmentioning
confidence: 99%